Nivel de conocimiento y manejo de pacientes con traumatismo encéfalo craneano grave en enfermeras (OS) de trauma shock y cuidados críticos, Iquitos 2022 - Rojas Rodriguez, Marlene Isabel (2024)
The objective of the research was to determine the relationship that exists between the level of knowledge and the management of patients with severe traumatic brain injury in nurses of the shock trauma and critical and intensive care services of the Loreto Regional Hospital, Iquitos -2022. The Method used was quantitative, with a descriptive correlational design; The sample is made up of 50 nursing professionals who work at the Loreto Regional Hospital. The techniques used were: interview, observation and the instruments: the level of knowledge questionnaire on severe cranial brain trauma in shock trauma and critical and intensive care nurses with a reliability of 89.6% and the verification sheet. of 86.0%. The results obtained were: average age of 43.9 years; 88.0% were female, 52% had 10 or more years of service, 52% had a specialty in critical care, 62% had 4 or more years of service in the area and 80% received training in the area. 46% had a medium level of knowledge, 34% had a high level, and 20% had a low level of knowledge about severe traumatic brain injury. In conclusion, it was found that there is a statistically significant relationship between the level of knowledge about severe traumatic brain injury and patient management (p= 0.008), in nurses of the shock trauma and critical and intensive care services of the Loreto Regional Hospital. Iquitos 2022.